Kontroversi dan Klarifikasi Thalaq sebagai Hal Halal Namun Dibenci Allah - Muhammad Yasril Harahap; Fadhilah Is; Fajriman Hulu; Muhammad Ridho Pranata; Ikhall Ahmad Fauzan Harahap; Ammar Huzein Nasution; Andri Gunawan; Putri Andini; Muhammad Kahfi Haikal Rambe; Muhammad Maulana Akbar (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research is conducted to address the controversy surrounding the thalaq hadith that circulates widely in society. Various opinions are spread about this hadith without properly delving into the quality of the hadith and solely relying on a single narration. However, thalaq (divorce) is a very sensitive matter, and misunderstanding a hadith without a proper understanding can lead to incorrect beliefs. Using a qualitative approach in the form of literature review, this study aims to explore a correct understanding of the controversial thalaq hadith. The findings of this research indicate that the controversy in society arises due to a lack of in-depth understanding of the origin of the hadith and a failure to comprehend the hadith comprehensively. There are other narrations that strengthen and clarify the thalaq hadith, making it evident that the hadith can be utilized as long as there are no conflicting narrations. Through this research, it is hoped that answers to the controversies circulating in society can be provided.